Coronavirus disease tracheostomy complications: a scoping review - Rosario, E; Ross, T; Komorowski, M; Tolley, N (Journal of laryngology and otology, 2023)
Coronavirus disease 2019 increased the numbers of patients requiring prolonged mechanical ventilation, with a subsequent increase in tracheostomy procedures. Coronavirus disease 2019 patients are high risk for surgical complications. This review examines open surgical and percutaneous tracheostomy complications in coronavirus disease 2019 patients. Medline and Embase databases were searched (November 2021), and the abstracts of relevant articles were screened. Data were collected regarding tracheostomy technique and complications. Complication rates were compared between percutaneous and open surgical tracheostomy. Percutaneous tracheostomy was higher risk for bleeding, pneumothorax and false passage. Surgical tracheostomy was higher risk for peri-operative hypoxia. The most common complication for both techniques was post-operative bleeding. Coronavirus disease 2019 patients undergoing tracheostomy are at higher risk of bleeding and peri-operative hypoxia than non-coronavirus disease patients. High doses of anti-coagulants may partially explain this. Reasons for higher bleeding risk in percutaneous over open surgical technique remain unclear. Further research is required to determine the causes of differences found and to establish mitigating strategies.